KINERJA WILAYATUL HISBAH DALAM PELAKSANAAN SYARIAT ISLAM DI KOTA BANDA ACEH PROVINSI ACEH - Oklin Riinan Winowoda; Akmal Quddus (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2021)
Aceh Province carries out special autonomy, in the context of implementing Islamic law, it is stated in the form of the Special Region of Aceh Law called Qanun. The kaffah application of Islamic law means that the local government will enforce the laws correctly and firmly against all Acehnese who violate Islamic law. The institution established to enforce Islamic law in Aceh is the Wilayatul Hisbah (Sharia Police) which has great responsibility in implementing Islamic law. Considering that the implementation of Islamic law in Banda Aceh City has not been optimal, the performance of Wilayatul Hisbah must be extra to improve the implementation of Islamic law in Banda Aceh City. For this reason, the purpose of this study is to find out how the performance of Wilayatul Hisbah in the Implementation of Islamic Law in Banda Aceh City Aceh Province . The research uses descriptive qualitative methods with an inductive approach. Data collection techniques using observation, documentation, interviews. Data analysis techniques using data reduction, data display/data presentation, conclusion drawing/verification. The results of this study are the performance of Wilayatul Hisbah in the implementation of Islamic law has been going well but there are several inhibiting and supporting factors in its implementation, including the lack of public understanding about existing laws or regulations, lack of personnel/human resources, the existence of a Qanun that is not yet clear in providing legal action/sanctions to violators of the Qanun, facilities and infrastructure as well as the Civil Service Police Unit Office and Wilayatul Hisbah City of Banda Aceh are inadequate, while the factors The supporters are the socialization, the sanctions given to violators who are firm in accordance with the Qanun, the support provided by the community, the ulama, traditional leaders, local governments, stakeholders, council members, officials and related institutions who care about the implementation of Islamic law in Banda City. Aceh. Keywords: Performance, Wilayatul Hisbah, Implementation